An Unusual U2AF2 Inhibits Splicing and Attenuates the Virulence of the Human Protozoan Parasite Entamoeba histolytica - González-Blanco, Gretter; García-Rivera, Guillermina; Talmás-Rohana, Patricia; Orozco, Ester; Galindo-Rosales, José Manuel; Vélez, Cristina; Salucedo-Cárdenas, Odila; Azuara-Liceaga, Elisa; Rodríguez-Rodríguez, Mario Alberto; Nozaki, Tomoyoshi; Valdés, Jesús (Frontiers in Cellular and Infection Microbiology, 2022)
E. histolytica is the etiological agent of intestinal amebiasis and liver abscesses, which still poses public health threat globally. Metronidazole is the drug of choice against amebiasis. However, metronidazole-resistant amoebic clinical isolates and strains have been reported recently, challenging the efforts for amebiasis eradication. In search of alternative treatments, E. histolytica transcriptomes have shown the association of genes involved in RNA metabolism with the virulence of the parasite. Among the upregulated genes in amoebic liver abscesses are the splicing factors EhU2AF2 and a paralog of EhSF3B1. For this reason and because EhU2AF2 contains unusual KH-QUA2 (84KQ) motifs in its lengthened C-terminus domain, here we investigated how the role of EhU2AF2 in pre-mRNA processing impacts the virulence of the parasite. We found that the 84KQ is involved in splicing inhibition/intron retention of several virulence and non-virulence-related genes. The 84KQ domain interacts with the same domain of the constitutive splicing factor SF1 (SF1KQ), both in solution and when the SF1KQ is bound to branchpoint signal RNA probes. The 84KQ-SF1KQ interaction prevents splicing complex E to A transition, thus inhibiting splicing. Surprisingly, the deletion of the 84KQ domain in EhU2AF2 amoeba transformants increased splicing and enhanced in vitro and in vivo virulence phenotypes. We conclude that the interaction of the 84KQ and SF1KQ domains, probably involving additional factors, tunes down Entamoeba virulence by favoring intron retention.